Pemanfaatan Aplikasi Telegram untuk Meningkatkan Kompetensi Guru dalam Pembuatan Bahan Ajar Video Menggunakan Smartphone - Mamat Mamat; Amar Nugraha (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
This study explores the use of the Telegram application to increase teacher competence in making video teaching materials using smartphones or smartphones. This study aims to improve understanding and development of technology for educators and education personnel in making teaching videos using smartphones. The subject of this case study is the Telegram group account